Frasa Posposisional Bahasa Mooi: Postpositional in Mooi Phrase - Sanjoko, Yohanis (Balai Bahasa Provinsi Papua, 2023)
Conducting a research focusing on local language is one effort in conserving nation’s cultural values. The so-called Mooi Language is one of the Papuan’s local languages spoken in the district of West Sentani, Jayapura Regency, Papua. It is specifically used by the people living in the village of Maribu, Waibron, Kendate, and Sabron Dosay. The Mooi speakers are counted around 1,200 people. Mooi Language is included into the family of non-Austronesian languages with its order of sentence structure is subject-object-predicator (SOP). This research is conducted with qualitative approach using descriptive method. The aim of this study is to describe form and type of postpositional phrase found in the language of Mooi. The research is organized into three strategic stages. They are collecting, analyzing and serving the result of data analysis. The stage of collecting data in this research is carried out with conversational method between the researcher and Mooi Language speakers, in this case, who act as informants. Instruments used in this research are list of postpositional phrases and list of sentences containing form and type of postposional phrase. Based on the analysis, types of postpostional phrase in Mooi Language are categorized into (1) postpositional phrase signaling functional relation, (2) postpositional phrase signaling relation of origin and direction of place, (3) postpositional phrase signaling relation of partitipation, manner or equipment, (4) postpositional phrase signaling relation of place, (5) postpositional phrase signaling relation of direction to certain place, (6) postpositional phrase signaling relation of likeliness, and (7) postpositional phrase signaling relation of target/goal.